Principio de presunción de inocencia y la credibilidad subjetiva de los testigos en el distrito judicial de Loreto Iquitos 2024 - Arevalo Sanchez, Billy Jackson (2025)
The objective of this research was to determine the relationship between the presumption of innocence and the subjective credibility of witnesses in the Judicial District of Loreto, Iquitos 2024. The question posed was: What is the relationship between both variables? This study, with a quantitative approach and a non-experimental descriptive-correlational design, analyzed data collected at a single point in time. Pearson's coefficient of evaluation indicated a strong positive and statistically significant association between the variables of interest (r = 0.802; p = 0.000), indicating that the subjective credibility of witnesses influences the application of the presumption of innocence. This shows that testimonial assessment can affect judicial decisions. It is concluded that it is necessary to establish objective criteria in testimonial assessment to reduce subjectivity in judicial processes. It is recommended to strengthen the training of judges and prosecutors, implement protocols based on scientific evidence, and promote the use of psychological expertise. These measures will help ensure fairer trials that respect the principle of the presumption of innocence.from Spanish to.